HUBUNGAN TINGKAT PENGETAHUAN DALAM MENYIKAPI BENCANA BANJIR DI MTSN 1 LANGKAT - Naufal Allamsyah; Nasution , Aditya Raihan; Muhammad Jidan Al Khoir; Bagas Prayoga Lubis; Selamat Ariady Tampubolon; Meutia Nandha (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
Indonesia is a country that has a fairly high level of vulnerability to natural disasters, especially floods. Floods often occur due to natural factors or human activities. School children are a vulnerable group who need adequate management education and knowledge in dealing with flood disasters. This research aims to determine the relationship between levels of knowledge in responding to flood disasters at MTsN 1 Langkat. This research uses quantitative methods with a pretest and posttest survey design on 66 students. The research instrument is a questionnaire consisting of 10 questions regarding definitions, causes, signs, initial actions, preparedness, mitigation and use of information related to flooding. Data analysis was carried out using paired sample t-test. The results show an increase in almost all material before and after being given education. definition of flood, before being given education 71% to 89%, signs of flooding, before being given education 41% to 61%, use of information, before being given education 71% to 88%. The average knowledge score from 2.14 pretest increased to 7.39 posttest. The paired sample t test produced a very statistically significant difference t = -29.462; p < 0.05, which indicates the effectiveness of disaster education in increasing students' knowledge. It is hoped that the program to increase knowledge about flood disasters can increase preparedness in school areas.